Outcome of Mode of Delivery in Nulliparous and Multiparous Women Presenting with Early and Late Cervical Dilatation - Shuchi, Ferdous Ara; Lovereen, Salma; Mina, Mst Nazumnnaher (Delta Medical College Journal, 2019)
Background: Knowledge of the patterns of normal and abnormal labour, and of women’s behavior, is fundamental to the formulation of mode of delivery. It is observed that women admitted to hospital early have a higher frequency of obstetric interventions in labour than those admitted later. Objective: To study the outcome of spontaneous onset of labour in nulliparous and multiparous patients. Materials and method: During the study period of 1st July 2008 to 31st Dec 2008, 568 pregnant women admitted in Kumudini Women’s Medical College were included in this study. Mothers were observed since admission with spontaneous onset of labour and followed up till they were released from the hospital. Labour outcome was measured and mode of delivery was compared among nulliparous and multiparous women. Results: Among the nulliparous women, normal vaginal delivery occurred in 71 (23%) patients presented with early cervical dilatation (0-3 cm) and in 142 (46%) patients presented with late cervical dilatation (>4 cm). In nulliparous women caesarean section were needed in 60 (45.8%) patients in early cervical dilatation group and in 35 (19.8%) patients in late cervical dilatation group. In multiparous women, normal vaginal delivery occurred in 66 (25%) patients presented with early cervical dilatation and in 133 (51%) patients presented with late cervical dilatation whereas cesarean section were done in 35 (34.7%) patients and in 25 (15.8%) patients in the two groups respectively. Duration of labour between nulliparous and multiparous was significantly different (8 hours vs. 6 hours). Indication of caesarean section were, 61 (40%) patients due to prolong labour, 48 (34%) due to foetal distress and 44 (26%) due to cephalopelvic disproportion. Conclusion: Normal vaginal delivery occurred more and duration of labour was shorter in patients admitted with advanced labour (cervical dilatation >4cm). Delta Med Col J. Jan 2019 7(1): 16-20